Bankruptcy Insolvency Taxation - Grant W. Newton (John Wiley, 2005)
The thousands of mergers, acquisitions, and start-ups that have characterized the past years of business have created an increasing number of corporations in financial trouble: specifically, a shortage of venture capital or quick cash. Consequently, bankruptcy protection is now viewed as a strategic move to protect corporations from their creditors and allow them to reorganize. Fully revised and updated with new case studies and the latest coverage of regulations, Bankruptcy and Insolvency Taxation, Fourth Edition provides the answers to the questions financial managers will have on the tax aspects of bankruptcy strategy.